Functional Polymorphism in the NFE2L2 Gene Associated With Tuberculosis Susceptibility - Ji, Guiyi; Zhang, Miaomiao; Liu, Qianqian; Wu, Shouquan; Wang, Yu; Chen, Guo; Sandford, Andrew J.; He, Jian-Qing (Frontiers in Immunology, 2021)
Background: Nuclear transcription factor erythroid 2 p45-related factor 2 (Nrf2), encoded by NFE2L2, functions as a key transcription factor and regulates expression of antioxidant genes. Our study aimed to investigate the association of single nucleotide polymorphisms of NFE2L2 with tuberculosis (TB) and latent tuberculosis infection (LTBI) and the underlying causal mechanisms. Methods: 1950 unrelated Chinese Han participants were included in our two independent study groups. Five tag polymorphisms were selected and genotyped. The functional effects of the rs13005431 polymorphism were confirmed by dual-luciferase reporter assays and mRNA level comparisons. Results: Rs13005431_C and rs2364723_G were associated with increased TB susceptibility (P = 0.010 and P = 0.041) after adjustment for confounding factors. rs6726395_A was associated with increased risk of active TB (P=0.035) in a comparison with the LTBI group. The frequency of haplotype rs1049751- rs13005431 AC was higher in the TB group (P =0.013), while frequency of haplotype AT was higher in the healthy control group (P =0.025). The luciferase activity of a plasmid with the rs13005431C-promoter was significantly lower than that of the rs13005431T-promoter. In addition, neutrophils with the CC / TC genotypes which were activated by GM-CSF showed a decreased level of NFE2L2 mRNA when compared with the rs13005431 TT genotype. Conclusions: Our study suggests that allele C of rs13005431 might increase the susceptibility to TB by down-regulating the transcriptional activity of NFE2L2.